Application of Preoperative Ultrasonography in the Diagnosis of Cervical Lymph Node Metastasis in Thyroid Papillary Carcinoma - Zhang, Ailong; Wu, Shenglan; You, Zhenhui; Liu, Wenkai (Frontiers in Surgery, 2022)
Background: The clinical value and application of preoperative ultrasound contrast in the diagnosis of cervical lymph node metastasis in thyroid papillary carcinoma is investigated. Methods: 126 cases of thyroid papillary carcinoma were selected, the sensitivity and accuracy of color ultrasound and ultrasound contrast were analyzed by comparing preoperative gray-scale ultrasound, color ultrasound and ultrasound contrast. Results: The accuracies of preoperative color ultrasound and ultrasound contrast in detecting lymph node metastasis were 74% and 82% respectively, and their sensitivities were 80% and 94% respectively. Lymph node metastasis was significantly more severe when the tumor diameter was >4 cm. The lymphatic metastatic rate of the patients with multifocal papillary carcinoma was 96.4%, whereas the lymphatic metastatic rate of the patients with thyroid gland lesion was 87.7%. The central foci of cervical lymph node metastasis included the following pathological subtypes: diffuse sclerosis type (89.3%, 25/28), high-cell type (72.2%, 8/11) and papillary type (40.0%, 4/10). Conclusions: Ultrasound contrast is more sensitive than color ultrasound in the diagnosis of cervical lymph node metastasis. Primary lesions ≥ 4 cm, lesion involvement, outer membrane and high-risk pathologic subtypes and lesions were considered as the criteria for ultrasound contrast application.